A Pembagian Waris Menurut Perspektif Hukum Islam Dan Adat Jawa - alfin (el-Bait: Jurnal Hukum Keluarga Islam, 2023)
Indonesia is a country that does not adhere to Islamic teachings in terms of law; in terms of inheritance itself, Indonesia adheres to three applicable laws, namely, inheritance law according to Islam, civil inheritance law originating from the Civil Code, and customary inheritance law. Islamic inheritance law and customary inheritance law certainly have different provisions and have their own characteristics. Therefore, the author wants to explain more deeply the division of inheritance in Islamic law and customary law in this article. In compiling this article, the author uses qualitative descriptive research, which is a type of library research with sources from journals, books, and other scientific works. In this study, researchers concluded that customary inheritance law and Islamic inheritance law have similarities in the distribution of inheritance, but customary inheritance law sometimes does not comply with the provisions in Islamic inheritance law, such as it is required that the heir must die, in customary inheritance law the heir does not have to die, meaning that the heir must die. Inheritance may be divided when the heir is still alive; not only that, in Islam, men get two parts, and women get one part, but in customary inheritance law, things like that sometimes do not apply. However, they are divided equally between men and women. What makes the difference between the distribution of Islamic and customary inheritance law is that in customary inheritance law, there is a principle of individuality and balance. With the principle of balance, the distribution of inheritance can differ from one another.